Enterprise-wide implementation of digital radiography in oral and maxillofacial imaging: the University of Florida Dentistry System. - Nair MK; Pettigrew JC Jr.; Loomis JS; Bates RE; Kostewicz S; Robinson B; Sweitzer J; Dolan TA (Journal of Digital Imaging, 2009)
The implementation of digital radiography in dentistry in a large healthcare enterprise setting is discussed. A distinct need for a dedicated dental picture archiving and communication systems (PACS) exists for seamless integration of different vendor products across the system. Complex issues are contended with as each clinical department migrated to a digital environment with unique needs and workflow patterns. The University of Florida has had a dental PACS installed over 2 years ago. This paper describes the process of conversion from film-based imaging from the planning stages through clinical implementation. Dentistry poses many unique challenges as it strives to achieve better integration with systems primarily designed for imaging; however, the technical requirements for high-resolution image capture in dentistry far exceed those in medicine, as most routine dental diagnostic tasks are challenging. The significance of specification, evaluation, vendor selection, installation, trial runs, training, and phased clinical implementation is emphasized.